2022
DOI: 10.1177/00380261221091012
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic politics and the institutionalisation of dignity: ‘Treated like the Queen’

Abstract: This article draws on theories of therapeutic politics to explore the role of institutionalised dignity as a medium for the social and political participation of traumatised people. Using the Australian Royal Commission into Institutional Responses to Child Sexual Abuse as a case study, the article offers a psychosocial account of shame and humiliation as key characteristics of the phenomenology of trauma, and presents dignity as the organising principle of a therapeutic politics. Through interviews with survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…While this study has focused on individual experience, there is support for victim needs being considered in a wider social and political context, with attention focused on a range of justice outcomes (16). This study also supports participation Inquiries as one way to promote healing for survivors of CSA, adding evidence for an approach that validates survivor testimony, and places dignity, as an antidote to shame, at the heart of participation (18,47). The theme of being believed and having accounts validated, supports the benefits of participation in Inquiries as citizens in addition to survivors, and lends further evidence to these processes as forms of therapeutic politics that can lead to personal healing and social change (19).…”
Section: Historical Institutional Abuse Inquiry Scholarship and Clini...mentioning
confidence: 54%
See 1 more Smart Citation
“…While this study has focused on individual experience, there is support for victim needs being considered in a wider social and political context, with attention focused on a range of justice outcomes (16). This study also supports participation Inquiries as one way to promote healing for survivors of CSA, adding evidence for an approach that validates survivor testimony, and places dignity, as an antidote to shame, at the heart of participation (18,47). The theme of being believed and having accounts validated, supports the benefits of participation in Inquiries as citizens in addition to survivors, and lends further evidence to these processes as forms of therapeutic politics that can lead to personal healing and social change (19).…”
Section: Historical Institutional Abuse Inquiry Scholarship and Clini...mentioning
confidence: 54%
“…The study concluded that participation should not focus exclusively on therapeutic outcomes for victims and survivors, but to take a broader perspective on victim needs. A further study looked at the experiences of participants in the Australian Royal Commission into Institutional Responses to CSA (18). The research included interviews with 26 survivors, with a majority reporting respectful and humane treatment, that contrasted with their previous experiences of minimization and denial by institutions.…”
Section: Historical Institutional Abuse Inquiriesmentioning
confidence: 99%